Trapping of the Fruit-flies, Dacus spp. (Diptera: Tephritidae) with methyl eugenol in Orchards - Ibrahim, A. G.; Singh, G.; King, H. S. (1979)
Field trapping of fruit-flies Dacus spp. (Diptera: Tephritidae) using methyl eugenol over a five week period was conducted in a fruit farm at Gombah, Selaugor, The results showed that traps with slit holes caught the greatest number of fruit-flies. Over 85% of the flies caught were male, Dacus dorsalis, Hendel. When different formulations of methyl eugenol; malaathion 50EC + methyl eugenol, Carbaryl85S + methyl eugenol, Dipterex SP 95%) methyl eugenol and distilled water + methyl eugenol were tested at Serdang significant differences 'were only detected in the number of flies trapped in those traps with methyl eugenol -I- insecticides and those 'with methyl eugenol alone. The technique use were effective in controlling the fruit-flies for there was a reduction of 20% of damaged carambola fruits.